Effectiveness of ESL students' performance by computational assessment and role of reading strategies in courseware-implemented business translation tasks. Issue 6 (18th August 2017) - Tsai, Shu-Chiao
ABSTRACT: This study reports on investigating students' English translation performance and their use of reading strategies in an elective English writing course offered to senior students of English as a Foreign Language for 100 minutes per week for 12 weeks. A courseware-implemented instruction combined with a task-based learning approach was adopted. Based on the same source texts in Chinese, students were asked to complete three English translation tasks rooted in real-life business contexts: announcements, sales letters, and public relation reports . A questionnaire about reading strategies was administered at the end of the instruction. Two types of computational assessment were used to evaluate students' translation performance. The results indicated that students' post-translation was quantitatively and qualitatively improved after receiving 12-week's courseware-implemented instruction, such as writing more words, using more different words of high level, enhancing lexical density, and making fewer errors. An independent sample t -test analysis indicated that a significant difference existed between students with higher and lower writing proficiency in two individual reading strategies related to metacognitive strategies that are higher order executive skills.